Simulation of Enhanced Growth of Marine Group II Euryarchaeota From the Deep Chlorophyll Maximum of the Western Pacific Ocean: Implication for Upwelling Impact on Microbial Functions in the Photic Zone - Dai, Jinlong; Ye, Qi; Wu, Ying; Zhang, Miao; Zhang, Jing (Frontiers in Microbiology, 2020)
Mesoscale eddies can have a strong impact on regional biogeochemistry and primary productivity. To investigate the effect of the upwelling of seawater by western Pacific eddies on the active planktonic marine archaeal community composition of the deep chlorophyll maximum (DCM) layer, mesoscale cold-core eddies were simulated in situ by mixing western Pacific DCM layer water with mesopelagic layer (400 m) water. Illumina sequencing of the 16S rRNA gene and 16S rRNA transcripts indicated that the specific heterotrophic Marine group IIb (MGIIb) taxonomic group of the DCM layer was rapidly stimulated after receiving fresh substrate from 400 m water, which was dominated by uncultured autotrophic Marine group I (MGI) archaea. Furthermore, niche differentiation of autotrophic ammonia-oxidizing archaea (MGI) was demonstrated by deep sequencing of 16S rRNA, amoA and accA genes, respectively. Similar distribution patterns of active Marine Group III (MGIII) were observed in the DCM layer with or without vertical mixing, indicating that they are inclined to utilize the substrates provided by cooccurring microorganisms living in the DCM layer. These findings shed light on the important role of mesoscale cyclonic eddies in stimulating the microbial functions in regional carbon cycle.